Persons with mental disorders and the exercise their rights - Ventura, Carla Aparecida Arena; Brito, Emanuele Seicenti de (Rev Rene, 2012)
This qualitative and descriptive research aimed at identifying the difficulties experienced by persons with mental health disorders at a Psychosocial Care Center in a municipality of the state of São Paulo in the exercise of their human rights. Data were collected through semi structured interviews and analyzed based on content analysis. Authors obtained the following themes: clear perception of the disease and experienced symptoms, felt and experienced discrimination; disrespect of their human rights, capacity and need to exercise citizenship, importance of a partnership between professionals and patients, humanized care. Authors concluded that although the rights of the persons with mental disorders are established in the Federal Constitution of Brazil and other laws, there are still problems to consolidate them, especially due to discrimination and the lack of knowledge by the patients, which impairs the exercise of their citizenship.